Relative Prices and the Macroeconomy: A Literature Review - Ogun, Oluremi (Global Economics Science, 2023)
This paper provides a review of the literature on the importance of relative prices in economic dynamics, focusing on three such prices: the relative price of one good/service to another, the terms of trade, and the real exchange rate. The narrative encompassed the theoretical, methodological and empirical spheres. The influential roles of relative prices in restoring internal and external equilibria were underscored and these attributes were deemed to be unparalleled in economic analysis. The terms of trade were particularly noted to be fundamental to economic growth, balance of payments, and, the real exchange rate.